MODEL LATIHAN CORE STABILITY PADA CABANG DAYUNG NOMOR KAYAK - Anas Wahyudi; Suci Rahmayanti; Ari Faizal; Andri Paranoan; lilik sudarwati; Nita Eka Aryanti; Reza Irwansyah (SPORT SCIENCE AND EDUCATION JOURNAL, 2023)
This final project aims to develop a core stability training model in the kayak rowing event. Besides that, it can also produce core stability training model products using media balance boards, medicine balls, rubber. The implementation of the Final Assignment project was carried out for 3 months from March to May 2020. The implementation of the Final Assignment project was carried out at PPOP Dayung DKI Jakarta. The method used in this study refers to the ADDIE model method. Namely starting from the analysis stage, model design, model development, model implementation that has been validated and evaluated. The core stability training model was validated by physical condition trainers and rowing experts. The results of the validation carried out resulted in 5 training models, namely: a) Torso rotation on balance board, b) Side twist with rubber on balance board, c) Shoulder front rise on balance board, d) Paddling with rubber on balance board, e) Combine full plank on balance board and medicine ball. The conclusion obtained through the application of the core stability training model to PPOP athletes is that core stability training is very much needed and suitable to be given to kayak rowing athletes.